Chrysophyllum Albidum and Its Potential Damage to the Kidney of Wistar Rats - lizabeth O, Nweke E; K, Opara Julia; Ifechukwu J, Obiesie (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: The study was aimed at determining the effect of graded doses of Chrysophyllumalbidum on the kidney. Materials and Methods: Twenty wistar rats (190-220 grams) were used in this study and they were randomly allocated into four groups of five rats each. Group A received food and distilled water only while groups B, C and D were treated with 100 mg/kg, 200 mg/kg 300 mg/kg of Chrysophyllumalbidum leaf extract respectively. The study lasted for three weeks after which the animals where sacrificed and their blood samples and kidney collected for examination. Results: The result from this study showed a significant decrease (p<0.05) in body weight in group of all treated groups. Also, there was a significant increase (p<0.05) in kidney weight in group C but a non-significant increase (p>0.05) in group B and D when compared to group A. In addition, the serum urea and creatinine level showed a significant decrease (p<0.05) in the treated groups when compared with that of group A. Histopathological findings revealed a mild to moderate changes in the cytoarchitecture of the kidney. Conclusion: This result of this study suggests that ethanolic leaf extract of Chrysophyllumalbidum may have the tendency of being toxic to the kidney tissue when consumed at higher doses.